Biosensing: Enhanced Charge Collection in MOF‐525–PEDOT Nanotube Composites Enable Highly Sensitive Biosensing (Adv. Sci. 11/2017). Issue 11 (23rd November 2017) - Huang, Tzu‐Yen; Kung, Chung‐Wei; Liao, Yu‐Te; Kao, Sheng‐Yuan; Cheng, Mingshan; Chang, Ting‐Hsiang; Henzie, Joel; Alamri, Hatem R.; Alothman, Zeid A.; Yamauchi, Yusuke; Ho, Kuo‐Chuan; Wu, Kevin C.‐W.
Abstract : In article number1700261, the Wu group presents poly(3, 4‐ethylenedioxythiophene) nanotubes (PEDOT NTs) conformally coated with porphyrin‐based metal–organic framework nanocrystals (MOF‐525), where MOF‐525 serve as an electrocatalytic surface and PEDOT NTs act as a charge collector to rapidly transport the electron from MOF nanocrystals. The innovative composites establish a new generation of porous electrodes for highly efficient electrochemical biosensing.